1986
DOI: 10.1073/pnas.83.1.130
|View full text |Cite
|
Sign up to set email alerts
|

The gene for human p53 cellular tumor antigen is located on chromosome 17 short arm (17p13).

Abstract: A clone that cross-hybridizes with a mouse p53 probe has been isolated from a cDNA library of simian virus 40-transformed human fibroblasts. This cloned human p53 cDNA was used as a probe to examine DNAs obtained from human-rodent somatic cell hybrids that have segregated human chromosomes. The results show that the human p53 gene is located on chromosome 17. In addition, Southern analysis of hybrids prepared from human cells containing a chromosome 17 translocation allowed regional localization of the human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
113
0
11

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(124 citation statements)
references
References 39 publications
0
113
0
11
Order By: Relevance
“…For example, the amplification expression of mir-17, mir-21 and mir-155 relatively cause tumour initiation and progression by inhibiting the expression of tumour suppressor genes, such as phosphatase and tensin homologue (PTEN), and programmed cell death 4 (PDCD4) (Meng et al, 2007;Petrocca et al, 2008;Frankel et al, 2008). In contrast, p53, also known as tumour protein 53, and is a tumour protein that in humans is encoded by the TP53 gene (McBride et al, 1986), is the most important and well-studied cancer gene that regulates the cell cycle involved in preventing cancer. Fundamentally, the action of p53 is to induce the expression of miRNAs, best described by the miR-34 family, which represses genes that can promote proliferation and apoptosis (He et al, 2007).…”
Section: Micrornas As Oncogenes and Tumour Suppressorsmentioning
confidence: 99%
“…For example, the amplification expression of mir-17, mir-21 and mir-155 relatively cause tumour initiation and progression by inhibiting the expression of tumour suppressor genes, such as phosphatase and tensin homologue (PTEN), and programmed cell death 4 (PDCD4) (Meng et al, 2007;Petrocca et al, 2008;Frankel et al, 2008). In contrast, p53, also known as tumour protein 53, and is a tumour protein that in humans is encoded by the TP53 gene (McBride et al, 1986), is the most important and well-studied cancer gene that regulates the cell cycle involved in preventing cancer. Fundamentally, the action of p53 is to induce the expression of miRNAs, best described by the miR-34 family, which represses genes that can promote proliferation and apoptosis (He et al, 2007).…”
Section: Micrornas As Oncogenes and Tumour Suppressorsmentioning
confidence: 99%
“…One of the tumor suppressor genes, human p53 gene has been assigned to 17p13.1 (Isobe et al, 1986;McBride et al, 1986) and its molecular abnormalities were frequently found in various tumor cells. The sequence polymorphisms within tumor suppressor genes are useful for the detection of loss of allele, and also it is important to be aware of rare sequence polymorphisms in the screening for gene mutations.…”
mentioning
confidence: 99%
“…The p53 tumor suppressor gene, located on the short arm of human chromosome 17 (1,2), encodes a 53-kd nuclear phos-phoprotein that functions as a negative regulator of cell proliferation (3,4). p53 is a transcription activating factor that acts as a "checkpoint" control late in GI to block the progression of cells through the cell cycle, particularly in the presence of DNA damage (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%